Analisis Implementasi Zona Selamat Sekolah (ZoSS) : (Studi Kasus : SDN Sukamentri 3-4-5 Garut) - Athaya Zhafirah; Difa Eka Aliansyah (Jurnal Konstruksi, 2026)
Traffic safety around the school environment, especially at SDN Sukamentri 3-4-5 Garut, remains a serious challenge due to the high risk of accidents when crossing the road. This study aims to evaluate the need for implementing a Zone Safe School (ZoSS) to improve pedestrian safety, especially children. The research method involved primary data collection through direct survey on road dimension, traffic volume, side obstacles, crossing behavior, driver behavior, and vehicle speed, as well as secondary data from literature review and student count. The results of the analysis showed three main conditions that did not meet safety standards: disorderly crossing behavior, delivery behavior that paid little attention to safety, and average vehicle speeds reaching 25 Km/h in the school area, exceeding the safe limit of 20 Km/h. Based on these findings, the implementation of ZoSS is considered important to create a more orderly and safe traffic environment. This research contributes to the field of transportation management and infrastructure safety by offering solutions to reduce the risk of accidents in school areas. With the implementation of ZoSS, it is expected to improve accessibility and traffic discipline, and create a safer environment for pedestrians.